Temporal Expression of a Master Regulator Drives Synchronous Sporulation in Budding Yeast - Minghao Chia; Folkert J. van Werven (G3: Genes, Genomes, Genetics, 2016)
Yeast cells enter and undergo gametogenesis relatively asynchronously, making it technically challenging to perform stage-specific genomic and biochemical analyses. Cell-to-cell variation in the expression of the master regulator of entry into sporulation, IME1, has been implicated to be the underlying cause of asynchronous sporulation. Here, we find that timing of IME1 expression is of critical importance for inducing cells to undergo sporulation synchronously. When we force expression of IME1 from an inducible promoter in cells incubated in sporulation medium for 2 hr, the vast majority of cells exhibit synchrony during premeiotic DNA replication and meiotic divisions. Inducing IME1 expression too early or too late affects the synchrony of sporulation. Surprisingly, our approach for synchronous sporulation does not require growth in acetate-containing medium, but can be achieved in cells grown in rich medium until saturation. Our system requires solely IME1, because the expression of the N6-methyladenosine methyltransferase IME4, another key regulator of early sporulation, is controlled by IME1 itself. The approach described here can be combined easily with other stage-specific synchronization methods, and thereby applied to study specific stages of sporulation, or the complete sporulation program.